Aortic Impingement in Displaced Traumatic Spine Fracture with Complete Spinal Cord Transection: A Case Report - Asma Anan Mohammed; Fatima R. Shulaiba; Mina Hikmat Ismaeal Alhety; Hayder Saleh Abdul Hadi Al Saadi; Bilal El Yafawi (Dubai Medical Journal)
Aortic impingement associated with traumatic thoracic spinal fractures is a rare and potentially lethal complication that creates management challenges in an already complex clinical problem. Traumatic aortic injury is one of the leading causes of death in blunt trauma. Magerl divided thoracic and lumbar fractures into 3 categories; the primary focus of this report, type C fractures, describes rotational injury and is one of the less common types, especially associated with aortic impingement as such. In this case, a young man was admitted following a near-fatal fall resulting in blunt force trauma to the midthoracic region. Emergency CT revealed a type C complete transection at the level of T11 and a grade I aortic injury. Definitive fixation of the spinal injury was delayed in favor of preventing further vascular injury by prioritizing the securing of hemodynamic stability. In traumatic thoracolumbar injuries, blunt traumatic aortic injury is often managed conservatively. However, blunt thoracic aortic injury is one of the leading causes of death from trauma, and each case requires its own case-by-case multidisciplinary management. In this occasion, management of the vascular insult was paramount to ensuring patient survival and favorable outcome.